Management of a patient with goiter : methodical recommendations for the preparation of students of higher education in the 6th year of study in the discipline «Internal Medicine» [Electronic resource] - Tykhonova, T. M.; Gorshunska, M. Yu.; Barabash, N. Ye.; Vasylenko, O. O.; Тихонова, Тетяна Михайлівна; Горшунська, Мар’яна Юріївна; Барабаш, Надія Євгенівна; Василенко, Ольга Олександрівна (Kharkiv : V.N. Karazin Kharkiv National University, 2024)
The methodological recommendations outline the main aspects of the management of patients with goiter syndrome, which include diagnosis and differential diagnosis of its individual forms, modern approaches to treatment. For students of the 6th year to prepare for practical classes in the discipline «Internal Medicine».
Ведення пацієнта з синдромом зобу : методичні рекомендації для підготовки студентів вищих навчальних закладів 6 курсу з дисципліни «Внутрішні хвороби» [Електронний ресурс]
Keywords: MEDICINE:: Internal medicine::Endocrinology; зоб; йододефіцит; гіпотиреоз; гіпертиреоз; тиреоїдит; goiter; iodinedeficiency; hypothyroidism; hyperthyroidism; thyroiditis